Effect of Butanol-Gasoline Blend Toward Performance Matic-Transmission Applied in Single Cylinder Capacity Engine - Gatot Setyono; Dwi Khusna; Navik Kholili; Lingga Putra Sanjaya; Fajar Galang Argil Putra (Infotekmesin, 2023)
The availability of fuel oil is decreasing while the level of consumption is increasing. This encourages the need for the development of alternative energy to minimize the crisis. This study investigates the characteristics of fuel and automatic transmission combustion engines. The fuel used is butanol variations B7, B12 and B18 (7%, 12%, and 18%) and pertalite (RON-90). The gasoline engine used has a capacity of 110 cc with a compression ratio of 9.5:1, an automatic transmission system, and air conditioning. The performance test equipment used is the Dynotest-chassis type 50L-BRT. Fuel variations are applied to an engine performance test by using engine speeds of 3000-9000 rpm. The results showed that the use of 18% butanol increased the output power and thermal efficiency by 8.3 kW and 923.95 kPa at 8000 rpm. torque and MEP (average effective pressure) increased by 8 N.m and 923.95 kPa at 5000 rpm. Meanwhile, SFC (specific fuel consumption) decreased by 0.35 kg/kWh at 8000 rpm.